2009
DOI: 10.1203/pdr.0b013e3181b337ec
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Closed Endotracheal Suction on Ventilation During Conventional and High-Frequency Oscillatory Ventilation

Abstract: ABSTRACT:In newborn infants, closed endotracheal tube (ETT) suction may reduce associated adverse effects, but it is not clear whether ventilation is maintained during the procedure. We aimed to determine the effect of ETT size, catheter size, and suction pressure on ventilation parameters measured distal to the ETT. Suction was performed on a test lung, ventilated with conventional (CMV) and high-frequency oscillatory ventilation (HFOV) using ETT sizes 2.5-4.0 mm, catheter sizes 5-8 French gauge (Fr), and suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
(28 reference statements)
1
14
0
Order By: Relevance
“…In both this article (28) and previous studies from the same group (21,29), it was notable that, when using the two smaller catheters (6 and 7FG) at the highest pressure, volume loss was less than or similar to that generated by an 8-FG catheter at the lowest pressure. Thus, recommendations for suctioning need to address both catheter size and suctioning pressure.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…In both this article (28) and previous studies from the same group (21,29), it was notable that, when using the two smaller catheters (6 and 7FG) at the highest pressure, volume loss was less than or similar to that generated by an 8-FG catheter at the lowest pressure. Thus, recommendations for suctioning need to address both catheter size and suctioning pressure.…”
mentioning
confidence: 51%
“…Those data were expanded with some studies considering lung mechanics after endotracheal suctioning (19,20). Some elegant theoretical (20,21) and practical studies followed, which highlighted the complexity of flows within suction catheters and endotracheal tubes during endotracheal suction.…”
mentioning
confidence: 99%
“…A smaller catheter provides more protection to the patient than does a lower suction pressure. 52,53 Catheter size is, unfortunately, not reported in all studies. In a small study of 17 infants, a catheter-to-ETT diameter ratio of 0.7 proved most effective without increasing the incidence of adverse outcomes.…”
Section: Suctioning Preparationmentioning
confidence: 99%
“…56 This may be explained by the probable presence of turbulent flow between the ETT and suction catheter during closed suctioning. 52 The concept that closed suctioning is better because it prevents volume loss may be incorrect. As soon as the catheter is inserted into the airway, lungvolume loss begins.…”
Section: Open Versus Closed Suctioningmentioning
confidence: 99%
“…Another study found overshoot in tidal volume using TTV mode after a rapid decrease in airway resistance, a change which occurs when suctioning ends [4] . We previously found that airway pressure distal to the ETT can become considerably negative (while circuit pressure remains unaffected) during closed suction with time-cycled, pressure-limited ventilation, but no published neonatal study to date has investigated the effect of ETT suction on ventilation in a TTV mode [5] .…”
Section: Introductionmentioning
confidence: 99%